Desempenho agronômico e caracterização de genótipos de girassol (Helianthus annuus L.) quanto a marcadores fenológicos, fisiológicos e bioquímicos em duas microrregiões edafoclimáticas do Rio Grande do Norte - Melo, Yuri Lima (Universidade Federal Rural do Semi-Árido, 2012)
The aim of this work was to characterize the agronomic performance of two sunflower genotypes grown under climatic conditions of salinity and water deficit by phenological, physiological and biochemical markers. In this sense, Catissol 01 and Helio 253 sunflower genotypes were cultivated during 3 months in two different areas in the RN state, a salt area (Ipanguaçu-RN IPÇ) and a water deficient area (Parnamirim-RN PAR). After 50 days of the emergency, 30 plants were selected to agronomic analysis like sunflower reproductive period (initial flowering date - DFI, full of bloom date DFP and physiological maturity date DMF), growth indicators and agronomic yield (height AP, diameter chapter DC, number of sheets NF, mass of achenes and grain yield per 1000 RG). Apical leaves from 10 plants were submitted to physiological and biochemical analysis like leaf water status indicators (relative content of water CRA, percentage of moisture %U) and membrane damage (electrolyte leakage VE). In apical, middle and basal leaves were made analysis like ionic stress indicators (Na+, K+, and Cl-) and osmotic adjustment (total soluble sugars-AST, reducing sugars AR, non-reducing sugars ANR, total free amino acids AALT and proline PRO). In PAR it was observed that the plants had their reproductive periods DFI, DFP and DMF retarded with respect to IPÇ to the two genotypes studied. In PAR, Catissol 01 and Helio 253 showed significant reductions in the variables AP (33 and 34%), DC (14 and 21%), NF (10 and 25%), mass of 1000 achenes (31 and 18%), RG (51 and 70%) and CRA (13 and 17%), respectively, compared to IPÇ. The VE was more pronounced in IPÇ than in PAR for both genotypes. It was noted that in PAR, K+ concentrations were higher in all leaves when compared to IPÇ for the two genotypes. Na+ and Cl- levels were higher in IPÇ than on PAR in all leaves for Catissol 01 and Helio 253. Both IPÇ and PAR and for both genotypes, it was not identified ion toxicity by K+/Na+ relation. It was observed that genotype Helio 253 has higher concentrations of AST in the leaves in IPÇ than in PAR. From the pool of AST, it was observed higher concentration of AR in the basal and apical leaves, while ANR was higher in median leaves. The Helio 253 genotype showed higher concentrations of AR in all leaves in PAR. The content of AST of Catissol 01 was higher in IPÇ than PAR, showing higher concentrations of AR in all leaves for the two places of cultivation. The genotype Helio 253 showed higher concentrations of AALT (apical and medians leaves) and PRO in IPÇ than in PAR. The genotype Catissol 01 did not provide significant differences in the content of AALT among IPÇ and PAR, with the exception of median leaves. But this genotype showed higher concentration of PRO in IPÇ (for basal and median leaves) than in PAR. Thus, we concluded that the genotypes showed better performance in IPÇ, that the concentrations of salts in IPÇ were not toxic, but caused signs of damage to the metabolism of both genotypes, that the water deficiency in PAR caused damage and disturbances at the growth and yield in two genotypes, but the variation of osmolytes seems to be associated with metabolic damage instead of the osmotic adjustment, there is evidence that the response of plants to environmental conditions depends on the genotype
Agronomic performance and characterization of genotypes of sunflower (Helianthus annuus L.) as the phenological, physiological and biochemical markers in two climatic region in the part of Rio Grande do Norte
Keywords: Sunflower (Helianthus annuus L.); salinity; drought; Girassol (Helianthus annuus L.); Salinidade; Seca; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA